An Assessment of Housing for Low-income Groups in Danang : Phase II Report - World Bank (Washington, DC, 2013)
In August 2004, in response to a request from the Government of Vietnam (GOV), the WB/ IDA launched preparatory activities for the Priority Infrastructure Investment Project (PIIP) in Danang. The PIIP is a multi-sectoral infrastructure investment initiative aimed at poverty reduction and the promotion of economic growth. The Project reflects the national goals set out in the Comprehensive Poverty Reduction and Growth Strategy (CPRGS), and is in line with the overall development priorities of the City's Five-Year (2006-200) Socio-Economic Development Plan (SEDP). The (PIIP) Project objectives are to: i) improve the living conditions and productivity of low income residents through better access to basic services; ii) promote economic growth through strategic investments that enhance mobility and increase private sector participation in the City's economic development; and iii) improve city and district level management through institutional and human resource development and capacity building. During the course of (PIIP) Project preparation activities, the Government expressed a desire to include a further sub-component to support the provision of housing for poor households not affected by the Project. This provided the rationale for the Assessment of Housing for Low Income Groups in Danang, (hereinafter referred to as the Low Income Housing Assessment Study (LIHAS)), which will parallel, support and inform preparation of the PIIP Project, while not being an integral part of it. The Study will take account of Government housing policy as it affects low-income households (LIH) in Danang. In this regard there has been a move away from direct Government involvement in house construction for the public sector service which was found to be financially unsustainable. The scope of work is based on two phases with the second phase consisting of options and recommendations: this second stage report contains: i) determination of the effective demand for low-income housing; ii) description of alternative technical standards for low income housing in the city; iii) overview of the need for financing of low income households, the demand for finance and different models of low income household finance; iv) definition of an outline low income housing policy for Danang City v) models of low-income housing production with varying degrees of public and private participation; vi) suggestions relating to the institutional framework for public housing provision and management.